Hubungan Pendidikan Nilai Agama dengan Perilaku Delinkuensi pada Remaja Madya di Sekolah Menengah Atas - Erik Wijaya; Niken Widiastuti; M. M. Nisfianoor (Provitae: Jurnal Psikologi Pendidikan, 2010)
The decrease of juvenile delinquency is affected by religion values education, and vice versa. The religion values education is one tool of moral guidance to bring welfare and peace for mankind by controlling self from arrogance, meanness, asocial behavior, and other forms of negative social behaviors. The juvenile delinquency is behavior of breaking social, legal, and religion norms which is conducted by people under age of 18 years. The study assessed 96 middle-adolescent of Y high school with characteristics of 15-18 year old and various religious backgrounds. This study used correlational design of non-experimental quantitative method, and the results were analyzed using Pearson Product Moment coefficient of correlation. The results were r (94)=-.923, p < .05, which showed a strong, significant, negative correlation between the religion value education and the juvenile delinquency.Keyword: religion value education, juvenile delinquency, middle adolescence.